Evaluation of yeast-based additives, as an alternative to ionophores, on rumen fermentation of ruminant diets using an in vitro gas production system - Cagliari, Amanda Regina; Magnani, Elaine; Rigon, Fernanda; Loregian, Kalista Eloisa; Casagrande, Ana Claudia; Amâncio, Bruna Roberta; Bueno da Silva, Juliana; Lisboa Santos, Veronica; Marcondes, Marcos Inácio; Paula, Eduardo Marostegan; Del Bianco Benedeti, Pedro; Branco, Renata Helena (Frontiers in Animal Science, 2023)
Introduction The study aimed to assess yeast-based additives' effects, as monensin alternatives, on rumen fermentation parameters, greenhouse gas emissions, and ruminal kinetics of ruminant diets using an in vitro system. Three experiments were conducted, each individually evaluating escalating levels of three yeast-based additives. Methods Three experiments were designed: Experiment 1 evaluated prebiotic blend 1—yeast culture [Saccharomyces cerevisiae (Scer)], beta-glucans, fructooligosaccharides, galactooligosaccharides, and mannanoligosaccharides; Experiment 2 investigated prebiotic blend 2—beta-glucan fractions and mannanoligosaccharides from Scer; Experiment 3 examined yeast cells—hydrolyzed, inactivated, and spray-dried yeast (Scer) cells. Uniform experimental design and procedures were employed across the three experiments. Each experiment had six treatments: monensin (Rumensin®, 25 mg/kg DM) as positive control, and yeast additive levels (0, 533, 1,067, 1,600, and 2,133 mg/kg on DM basis) added to ruminant diets (60% corn silage and 40% concentrate). An in vitro gas production (GP) system with 50 AnkomRF bottles assessed total GP (at 24 and 48 hours), kinetics, fermentation profiles, methane (CH4), and carbon dioxide (CO2) concentrations. Comparison with monensin utilized Dunnett’s test (5%). Yeast additive levels were analyzed for linear and quadratic responses. Results In Experiment 1, the 1,600 mg/kg yeast additive had lower concentrations of propionate, isobutyrate, valerate, and branched-chain volatile fatty acids (BCVFAs), and a higher acetate concentration and acetate-to-propionate ratio than monensin. In Experiment 2, the 1,600 mg/kg yeast additive led to lower total VFA and isovalerate concentrations than monensin. Additionally, compared to the 1,067 mg/kg yeast additive, monensin showed lower isovalerate concentration and higher NH3-N concentration. In Experiment 3, the 533 mg/kg yeast additive resulted in lower valerate and BCVFA concentrations, and higher CH4 and CO2 concentrations than monensin. Monensin had lower total VFA, butyrate, and acetate-to-propionate ratio, and higher propionate concentration compared to the 2,133 mg/kg yeast additive. Discussion Collectively, these findings suggest yeast-based additives could be monensin alternatives, enhancing animal nutrient utilization efficiency and contributing to improved livestock sustainability.